2001
DOI: 10.1097/00129492-200105000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Early Identification of Hearing Impairment in Patients With Type 1 Diabetes Mellitus

Abstract: Combined use of different procedures for monitoring central and peripheral portions of the auditory pathway in diabetic patients showed alterations in cochlear micromechanics and the retrocochlear auditory pathway. Hearing impairment in diabetic patients is usually mild and subclinical, and can be detected early by accurate and objective audiometric methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
69
3
6

Year Published

2002
2002
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(86 citation statements)
references
References 17 publications
8
69
3
6
Order By: Relevance
“…Other authors showed abnormal values of BAEP latencies and interlatencies (peaks: I, III, V, I-III, I-V) in 48% of the patients with Type I diabetes but without any correlation with clinical and biochemical parameters characterising diabetes [22]. The latest results provide similar conclusions [25,26]. But there are also reports showing no disturbances in peripheral and central hearing organ in diabetes [14,27,28].…”
Section: Discussionmentioning
confidence: 73%
“…Other authors showed abnormal values of BAEP latencies and interlatencies (peaks: I, III, V, I-III, I-V) in 48% of the patients with Type I diabetes but without any correlation with clinical and biochemical parameters characterising diabetes [22]. The latest results provide similar conclusions [25,26]. But there are also reports showing no disturbances in peripheral and central hearing organ in diabetes [14,27,28].…”
Section: Discussionmentioning
confidence: 73%
“…Similar results were reported by Lisowska et al in their study, where DPOAE amplitudes (Ldp) were significantly reduced in diabetic group, but no correlation was ascertained between DPOAE amplitude (Ldp) and duration of diabetes. 13 Abo-Elfetoh et al also reported decrease in DPOAE amplitude (Ldp) in diabetes especially at higher frequencies suggesting peripheral auditory system dysfunction.…”
Section: Discussionmentioning
confidence: 95%
“…The association between hearing loss and diabetes mellitus (type I and type II) has been debated since it was first mentioned by Jordan in 1857, being subject of debate and remaining controversial to this day, despite numerous previous studies [8][9][10][11] . In 1864, it was identified the first scientific documentation connecting glucose metabolism disorders to inner ear diseases; observing the relation between sensorineural deafness and diabetes, thus establishing the link between hearing loss and hyperglycemia.…”
Section: Audiological Implicationsmentioning
confidence: 99%
“…In 1864, it was identified the first scientific documentation connecting glucose metabolism disorders to inner ear diseases; observing the relation between sensorineural deafness and diabetes, thus establishing the link between hearing loss and hyperglycemia. Since then, several authors reported vestibular-cochlear secondary alterations to diabetes mellitus 11,12 . Among glucose metabolism disorders, diabetes mellitus is the affection most commonly related with auditory disorders…”
Section: Audiological Implicationsmentioning
confidence: 99%
See 1 more Smart Citation